2014
DOI: 10.1002/uog.13360
|View full text |Cite
|
Sign up to set email alerts
|

Fetal MRI insular cortical morphometry and its association with neurobehavior in late-onset small-for-gestational-age fetuses

Abstract: Objective To evaluate insular cortical morphometry assessed by magnetic resonance imaging (MRI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…The metabolic changes detected in this study are also in line with other brain reorganizational differences reported in SGA fetuses, including microstructural changes in various brain areas, differences in brain sulcation and in cerebellar and brainstem size [12,13,14,39]. …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The metabolic changes detected in this study are also in line with other brain reorganizational differences reported in SGA fetuses, including microstructural changes in various brain areas, differences in brain sulcation and in cerebellar and brainstem size [12,13,14,39]. …”
Section: Discussionsupporting
confidence: 75%
“…Thus, small fetuses with abnormal uterine artery Doppler ultrasound [4], birth weight below the 3rd centile [5] or signs of brain redistribution [3] are associated with poorer perinatal outcome. It has been speculated whether those SGA fetuses without signs of poor perinatal outcome showed merely milder forms of the same disease, were constitutionally small fetuses or represented another pathogenic pathway leading to abnormally low fetal growth [8,12,13]. The findings of the present study challenge the notion that SGA fetuses without signs of severity are merely constitutionally small.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Recent research has evaluated the anatomical and functional substrates in this pathology, showing the existence of structural anomalies in fetal brain fissures and cerebral connections as well as functional anomalies that suggest suboptimal neural networking and cortical maturation [17][18][19] . FGR may also lead to direct neuronal damage increasing the leakage of specific markers, especially during early-onset FGR and acute-labor hypoxia [20][21][22] , but there is less evidence of this mechanism in late-onset FGR, possibly because the hypoxia is milder or of a shorter duration prior to birth.…”
Section: Interpretation Of the Findings And Comparison With The Litermentioning
confidence: 99%
“…Use of these technologies has revealed alterations in the cerebral NAA:choline ratio and gyrification in fetuses with congenital heart disease, 10 temporal lobe volumes in fetuses with congenital cytomegalovirus infection, 11 and ADC values and parenchymal volume in antenatal ventriculomegaly. 12,13 Historically, most fetal imaging studies have been undertaken at 1.5T. However, although an increasing number of studies have been performed at 3T field strength, 14-20 which has benefits over 1.5T due to improved signal-to-noise and is likely to be advantageous for depicting fetal anatomy, 21 On the basis of disturbances to fetal glucose and fatty acid metabolism associated with maternal diabetes and the neurocognitive profile of offspring, we aimed to investigate the feasibility of comprehensive fetal brain assessment by acquiring measurements of NAA/Cho, NAA/Cr, and Cho/Cr ratios; regional apparent diffusion coefficient measurements; and volume of the cerebrum during the third trimester of pregnancy from women with diabetes and from healthy controls by using 3T MR imaging.…”
mentioning
confidence: 99%